Systems genetic analysis of hippocampal neuroanatomy and spatial learning in mice - Delprato, Anna (Genes Brain Behav, 2015)
Variation in hippocampal neuroanatomy correlates well with spatial learning ability in mice. Here we have studied both hippocampal neuroanatomy and behavior in 53 isogenic BXD recombinant strains derived from C57BL/6J and DBA/2J parents. A combination of experimental, neuroinformatic, and systems genetics methods were used to test the genetic bases of variation and covariation among traits. Data were collected on seven hippocampal subregions in CA3 and CA4 after testing spatial memory in an 8-arm radial maze task. Quantitative trait loci (QTLs) were identified for hippocampal structure, including the areas of the intra- and infrapyramidal mossy fibers, stratum radiatum, and stratum pyramidale, and for a spatial learning parameter, error rate. We identified multiple loci and gene variants linked to either structural differences or behavior. Gpc4 and Tenm2 are strong candidate genes that may modulate intra- and infrapyramidal mossy fiber areas. Analysis of gene-expression networks and trait correlations highlight several processes influencing morphometrical variation and spatial learning.